2022
DOI: 10.3390/foods11192974
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Application of Metabolomics on Bioactive Ingredients of Foods

Abstract: Metabolomics, as a new omics technology, has been widely accepted by researchers and has shown great potential in the field of nutrition and health in recent years. This review briefly introduces the process of metabolomics analysis, including sample preparation and extraction, derivatization, separation and detection, and data processing. This paper focuses on the application of metabolomics in food-derived bioactive ingredients. For example, metabolomics techniques are used to analyze metabolites in food to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Sample solutions were ground in a frozen tissue grinder for 6 min (−10 • C, 50 Hz), followed by low-temperature ultrasonic extraction for 30 min (5 • C, 40 kHz). The samples were allowed to stand at −20 • C for 30 min, followed by centrifugation for 15 min (4 • C, 13,000× g) [5]. The supernatant was pipetted into an injection vial with an internal cannula for analysis.…”
Section: Metabolite Extraction and Analysis By Liquid Chromatography-...mentioning
confidence: 99%
See 3 more Smart Citations
“…Sample solutions were ground in a frozen tissue grinder for 6 min (−10 • C, 50 Hz), followed by low-temperature ultrasonic extraction for 30 min (5 • C, 40 kHz). The samples were allowed to stand at −20 • C for 30 min, followed by centrifugation for 15 min (4 • C, 13,000× g) [5]. The supernatant was pipetted into an injection vial with an internal cannula for analysis.…”
Section: Metabolite Extraction and Analysis By Liquid Chromatography-...mentioning
confidence: 99%
“…The stability of the model was assessed using principal component analysis (PCA) and orthogonal least squares discriminant analysis (OPLS-DA) with seven cycles of crossvalidation [5]. The selection of significantly different metabolites was determined based on the variable weight (variable importance in projection [VIP]) values obtained from the OPLS-DA model and the p-value obtained from the student's t-test.…”
Section: Metabolite Extraction and Analysis By Liquid Chromatography-...mentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolomic methods are fundamental apparatuses in the food sector to identify metabolites and perform subjective and quantitative analyses [ 9 , 10 ]. Detection systems, such as LC−MS, HPLC−ESI/APCI−MS, and UPLC−LTQ−MS, with high detection sensitivity and phenomenal detachment execution, are commonly used to detect small molecule metabolites in fruits [ 11 , 12 ]. Among them, ESI and APCI techniques are relatively more suitable soft ionization techniques for the analysis of protonated molecular ions of the most relevant plant secondary metabolites, and numerous studies have demonstrated their superiority for several identification errands [ 13 ].…”
Section: Introductionmentioning
confidence: 99%